UNIVERSITY BUSINESS INCUBATORS: HOW THEIR SUPPORT AND FIRST-TIME FOUNDERS' ORIENTATION MATTER FOR NEW VENTURE PERFORMANCE - Fajri, Detha Alfrian; Adam, Muhamad Dafa (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This study addresses both empirical and practical challenges related to the performance of new ventures, focusing on the roles of University Business Incubators (UBIs) and Entrepreneurial Orientation (EO) among first-time founders. The study investigates how the support provided by UBIs and the entrepreneurial mindset of founders influence the success of new ventures. Employing an explanatory research design with a quantitative approach, this study examines the relationships between UBIs, EO, and New Venture Performance (NVP). Data were collected from 100 respondents associated with Brawijaya University's incubator program and analyzed using multiple linear regression with SmartPLS 3. The variables studied include University Business Incubator (X1), Entrepreneurial Orientation (X2), and New Venture Performance (Y). The results indicate that UBIs have a significant positive effect on NVP, evidenced by a t statistic of 5.468 and a p value of 0.000. EO also significantly impacts NVP, with a t statistic of 4.291 and a p value of 0.000. Furthermore, the combined effect of UBIs and EO on NVP is substantial, as shown by a Goodness of Fit (GoF) Index of 0.686, suggesting that these factors together account for a significant portion of the variance in venture performance. The discussion highlights that while UBIs provide essential structural support, such as mentorship and resources, EO fosters a proactive and innovative culture crucial for venture success. Practically, universities should invest in robust incubator programs and promote entrepreneurial education to maximize startup success. Theoretically, this study contributes to the understanding of how structural and cultural elements within educational institutions jointly influence new venture performance, suggesting a dual approach of support and cultural development.